Utilization of Webcam Cameras as X-Ray Image Capture Based on kV Settings and Shutter Sensors - Dwara, Ni Made Wagiswari; Mak’ruf, Muhammad Ridha; Indrato, Tri Bowo (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
The end product of an x-ray image is often a sheet of film. The film must go through chemical processing in order to produce an image. To get around these issues, efforts were undertaken to create digital x-ray detectors utilizing far less expensive gadgets. The aim of this research is to present a study that explores the development of a digital X-ray imaging system using cost-effective sensors, assesses its image quality, and discusses the potential benefits of this technology for capturing X-rays.Utilizing sensors that try to determine the difference in the final image's quality as well as voltage variances. The system may present negative image findings from webcam camera captures that have already passed the image processing process with the Matrix Laboratory (MATLAB) Application, which is the study's main contribution. With a set mA of 25mA, a period of irradiation of 1 second, and a moderate intensity of illumination light, the measurement ranges employed are 60, 65, and 70 kV. Knowing the value of kv and optimal sensor settings based on image results is the study's goal. The measurement findings demonstrate that the Philip brand DR's picture results and those from the X-ray picture Capture Tool may be compared thanks to the MSE value of 34.8775 and the parameters Phototransistor BPT1331 at 70kV and 25mA. And the LDR, 66kV, 25mA configuration has the lowest MSE value at 61.7615. The study's findings suggest that the gadget can be used to record X-rays.